A statistical model for combustion resonance from a DI diesel engine with applications. (August 2015) - Bodisco, Timothy; Low Choy, Samantha; Masri, Assaad; Brown, Richard J.
Abstract: Introduced in this paper is a Bayesian model for isolating the resonant frequency from combustion chamber resonance. The model shown in this paper focused on characterising the initial rise in the resonant frequency to investigate the rise of in-cylinder bulk temperature associated with combustion. By resolving the model parameters, it is possible to determine: the start of pre-mixed combustion, the start of diffusion combustion, the initial resonant frequency, the resonant frequency as a function of crank angle, the in-cylinder bulk temperature as a function of crank angle and the trapped mass as a function of crank angle. The Bayesian method allows for individual cycles to be examined without cycle-averaging—allowing inter-cycle variability studies. Results are shown for a turbo-charged, common-rail compression ignition engine run at 2000 rpm and full load. Abstract : Highlights: Propose the use of Bayesian modelling for the isolation of the resonant frequency in an in-cylinder pressure signal. Describe an appropriate statistical model for the isolation of the resonant frequency. Show how the statistical model is implemented. Use the model to isolate the start of combustion, start of diffusion combustion and to infer the in-cylinder temperature. Confirm the importance of a modern technique for engine research.